Assessment of the Toxicological Effects of Cypermethrin Nanoformulation on Hypselobarbus pulchellus using Selected Biomarkers: Toxicity of Cypermethrin Nanoformulation on Hypselobarbus pulchellus - Jesna, P. K.; Das, Basanta Kumar; Sarkar, Dhruba Jyoti; Krishnani, Kishore Kumar; Chadha, Narinder Kumar; Hemaprasanth, Kannur (Fishery Technology, 2025)
Pesticides are widely used in aquaculture farms against ectoparasites. However, due to the development of resistance in ectoparasites against the traditional pesticide formulations, pesticides are being applied at a higher dose or in combinations. Nano formulation of pesticides with enhanced properties is a viable option to reduce the volume of traditional pesticides applied in aquaculture. Hence, the present study developed a nano formulation of the pesticide cypermethrin and evaluated the toxic effects in the fish Hypselobarbus pulchellus. The acute toxicity study recorded the mortalities at 24h intervals for 96h. The 96h LC50 value was estimated to be 0.003 mg L-1. Chronic toxicity studies were also conducted exposing H. pulchellus to sublethal concentrations for 45 days. The brain acetylcholine esterase activity was significantly reduced (p ˂ 0.05) in the cypermethrin nano formulation exposed fish. The nano formulation exposure also caused a significant increase in the liver and kidney superoxide dismutase activity. Elevated catalase and glutathione-s-transferase levels were observed in the liver and gills, with no conspicuous change in the kidneys. The serum enzymes aspartate aminotransferase and alanine aminotransferase were elevated significantly by cypermethrin exposure. The serum triglycerides, cholesterol, and protein content were reduced significantly. Similarly, the red blood cell, haematocrit, haemoglobin, and platelet count also showed significant reduction on cypermethrin exposure. These findings on the toxic impacts may help to understand the effect of micro-formulated antiparasitic drugs in fin fish.